Deixis and Digital Persuasion: Sociopreneurship Messages of @aldwinnv on Instagram and TikTok - Astutik, Ari; Dewanto; Erwanto S, Lambang (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study examines the role of deixis in shaping persuasive sociopreneurship communication on Instagram and TikTok, focusing on six posts (three from each platform) by the Indonesian sociopreneur @aldwinnv. Deixis, as a pragmatic linguistic feature, situates utterances in relation to the speaker, audience, and context, making it essential for persuasive strategies in digital communication. Employing a qualitative descriptive approach within the pragmatic discourse framework, the study identifies personal, temporal, spatial, discourse, and social deixis in the data. Findings indicate that personal deixis, particularly saya (I) and kita (we), builds relational intimacy and credibility. Temporal deixis, such as sekarang (now) and hari ini (today), creates urgency and motivates immediate action. Spatial deixis (e.g., di sini, tempat ini) authenticates the speaker’s experience by grounding narratives in real contexts. Social deixis (e.g., teman-teman, sahabat, bro) varies between platforms, reflecting formality on Instagram and casual solidarity on TikTok. Discourse deixis (e.g., seperti yang saya bilang tadi) strengthens coherence in motivational storytelling. These findings show that deixis operates as a persuasive device that enhances ethos, pathos, and communal identity in sociopreneurship content. The study contributes to digital pragmatics by demonstrating how subtle linguistic cues support persuasive entrepreneurship narratives and offers pedagogical implications for media literacy and entrepreneurship education.